ChemInform Abstract: Stereocontrolled Synthesis of the Oxathiabicyclo[3.3.1]nonane Core Structure of Tagetitoxin. Issue 17 (28th April 2014) - Yamada, Hitomi; Adachi, Masaatsu; Nishikawa, Toshio
Abstract The fully functionalized core structure (I) of tagetitoxin is synthesized from tri‐O‐acetyl‐D‐galactal.